PERBEDAAN SEBELUM DAN SESUDAH PERLAKUAN TAWAS DALAM MENURUNKAN PH, TDS, DAN TSS AIR LIMBAH DI BATCHING PLANT PT.X TAHUN 2022 - Ryan Muhaidi (2022)
Wastewater is a liquid left over from processed activities that is no longer used, the source of wastewater usually comes from an activity such as trade, offices, settlements and industry, or the rest of rainwater mixed with a residual activity. The largest waste producer in Indonesia is in industrial activities, one of which is PT.X which produces wastewater from production activities, but with the quality of PT.X's waste there is no wastewater treatment to produce quality wastewater in accordance with the regulation of the Minister of the Environment 5 of 2014 regarding wastewater quality standards. This study aims to determine the differences in the dose variation of alum in reducing the pH, TDS, and TSS levels of wastewater at the PT.X batching plant in 2022. This type of research is quantitative analysis with experimental study design. The statistical test that used was shapiro-wilk, paired sample t-test and friedman, in the treatment group p < α 0,05, which means that there is an average difference in each group of parameters pH, TDS, and TSS wastewater PT.X. Therefore, it is suggested to the company to implement a processing system using the alum method to produce quality standards according to government regulations.